2009
DOI: 10.1089/thy.2008.0206
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women on Thyroxine Substitution Are Often Dysregulated in Early Pregnancy

Abstract: In 49% of pregnant women on thyroxine substitution, serum TSH values were outside the reference range when first tested, generally in the first trimester. Fetal loss was significantly greater in pregnant women with abnormal TSH values compared to those with normal TSH values. Thyroid function in pregnant women on thyroxine substitution should be monitored early in pregnancy and carefully followed during pregnancy. The thyroxine dose should be increased as needed early in pregnancy to avoid hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 21 publications
6
70
0
1
Order By: Relevance
“…On the other hand, around 2% of pregnant women in the DNBC had a history of thyroid disease at the time they became pregnant and another 2% developed thyroid disease in the 5-year period following the pregnancy. Women with known thyroid disease prior to a pregnancy may not be adequately treated by the time they become pregnant, and women first time diagnosed and treated for thyroid disease after a pregnancy could have suffered from undetected and untreated thyroid dysfunction during the pregnancy (35,36,37,38). Such potential thyroid abnormalities may adversely affect fetal development, particularly early brain development.…”
Section: Clinical Perspectivementioning
confidence: 99%
“…On the other hand, around 2% of pregnant women in the DNBC had a history of thyroid disease at the time they became pregnant and another 2% developed thyroid disease in the 5-year period following the pregnancy. Women with known thyroid disease prior to a pregnancy may not be adequately treated by the time they become pregnant, and women first time diagnosed and treated for thyroid disease after a pregnancy could have suffered from undetected and untreated thyroid dysfunction during the pregnancy (35,36,37,38). Such potential thyroid abnormalities may adversely affect fetal development, particularly early brain development.…”
Section: Clinical Perspectivementioning
confidence: 99%
“…Therefore, evaluation of thyroid function tests during The iodine requirement during normal pregnancy: The pregnancy is great importance to prevent the above Glomerular Filtration Rate (GFR) and the subsequent abnormalities (LeBeau and Mandel, 2006;Springer et al, increase in renal blood flow, alter the normal clearance of 2009; Hallengren et al, 2009). renal iodide to be increased and this normal physiological thyroid function during pregnancy require the condition well happened during early phase of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…This was largely due to the disproportionate impact of cases where the TSH was O10 mU/l, but significantly increased already when TSH was O4.5 mU/l (52). Similarly, another small study suggested more miscarriages with both suppressed and elevated TSH in pregnant women on T 4 replacement (53).…”
Section: Evidence For Adverse Effects Of Sch During Pregnancymentioning
confidence: 98%